Quality parameters of the tibiae and femora of ostriches - Almeida Paz,ICL (2008)
An experiment was carried out to establish mean bone quality values of the tibiae and femora of ostriches and to evaluate these bones. The right leg bones of 10 males and 10 female African Black ostriches were evaluated. Birds were radiographed immediately after slaughter (during bleeding), with the aid of a portable X-ray apparatus. The obtained radiographs were scanned and bone mineral density means were obtained using software. Bone strength, Seedor index, and dry matter percentage were evaluated and correlated to weight gain during the finishing period (3-13 months of age). Mean values of the evaluated bone quality traits, not previously found in literature, were established. There were no significant differences between males and females in performance or bone quality parameters. It was concluded that male and female ostriches present similar performance and bone quality at slaughter age.